HARVEST COMPONENTS AND PRODUCTIVITY OF COMMON WHEAT VARIETIES GROWN IN THE CENTRAL REGION - Makhammatova M. U.; Kholmurodova G. R. (Galaxy International Interdisciplinary Research Journal, 2024)
The article presents data on yield elements and productivity of soft wheat varieties grown in the central region. According to the observations made during the years in the conditions of the central region during the research, according to the indicator of the number of productive stems per 1 m2 of the autumn soft wheat varieties, the newly created Yuksak variety and Yaksart varieties, 1 ear length Yuksak, Yaksart, Krasnodar-99 and Hazrati, who participated as a model variety Bashir varieties, the number of grains in one spike Chillaki, Asr, Yuksak and Yaksart varieties, Gozgon, Yuksak, Yaksart, Asr and Krasnodar-99 varieties according to the weight of grains in 1 spike, Yuksak, Krasnodar-99, Zamin-1 varieties according to the weight of 1000 grains, the superiority of Yuksak, Asr, Yaksart, Gozgon, Vassa and Krasnodar-99 varieties in increasing productivity was noted, and the advantage of using them in genetic-selection studies was mentioned.